Treatment and outcome of CPD-associated peritonitis - Finkelstein Fred; Troidle Laura (BMC, 2006)
Abstract CPD-associated peritonitis is a leading cause of morbidity and mortality for ESRD patients maintained on CPD therapy. The percentage of ESRD patients maintained on CPD therapy is declining. The reasons are unclear, but may be due to concerns about CPD-associated peritonitis. The incidence of CPD-associated peritonitis has decreased largely attributed to technical advances and the identification of risk factors including exit-site infection, colonization with Staphylococcus aureus and depression. The typical spectrum of organisms causing peritonitis include gram-positive organisms (67%), gram-negative organisms (28%), fungi (2.5%) or anaerobic organisms (2.5%). Culture-negative episodes do occur: up to 20% of the episodes of peritonitis in some series are culture-negative. The treatment of CPD associated peritonitis is rather standardized with current recommendations by the International Society of Peritoneal Dialysis universally adopted. Approximately 80% of the patients developing peritonitis will respond to antimicrobial therapy and remain on CPD therapy, while 10 to 15% of the patients require catheter removal and transfer to hemodialysis. Approximately 6% of the patients expire as a result of peritonitis. The outcome is different based on organism with gram-negative and fungal episodes having a worse outcome than gram-positive episodes. The development of CPD-associated peritonitis can be linked to traditional risk factors such as exit-site infection and poor technique. Bacterial biofilm has also been suggested as a cause of peritonitis. Our current antimicrobial protocols may not permit adequate dosing to penetrate the biofilm and be a reason for recurrent or repeat episodes of peritonitis. It is important that we improve our understanding of factors responsible for the development and outcome of CPD-associated peritonitis in order for this renal replacement therapy to remain a viable option for patients with ESRD.